The Effect Of Arm Muscle Power On Smashing Skills In Volleyball At Smp Negeri 32 Seluma - Elsa Sari; Dody Ertanto; Feby Elra Perdima (Utami Publisher, 2026)
This study aims to determine the Effect of Arm Muscle Power on Smash Skills in Volleyball Games at SMP Negeri 32 Seluma. This type of research is an experimental study with a sample of 17 volleyball extracurricular students at SMP Negeri 32 Seluma. The results of the study showed that the average value of students' Smash Skills increased from the initial test (pretest) with an average of 11.80 before being given arm muscle power training for 8 meetings and then increased in the final test (posttest) to 14.20. This increase occurred due to the physical adaptation of the application of the arm muscle power training method to the physical condition of the body that supports Smash Skills at SMP Negeri 32 Seluma. The results of the hypothesis test analysis obtained a t-table value with degrees of freedom 17-2 (dk = 15) at a significance level of α = 0.05 of 1.753. This means that t-count = 7.91> t-table = 1.753. Thus, it can be stated that the hypothesis proposed by the author, namely